Developing and deploying bioformatics applications as web services - Isaac Eliezer Sutedja. (2008)
In this project, we investigate how existing standalone Bioinformatics applications can be wrapped and deployed as web services. Next, we study how to publish these web services, and how a potential user can discover them. We will also explore how to develop client applications to use the functionalities of the web services. Finally, we investigate how web services can be utilized to build a pipeline of bioinformatics applications.